Protected bay and hunting-fishing nodes in the southern islands of Patagonia. The Tilly East canoe site on Carlos III Island, Strait of Magellan (53°S) - Torres Elgueta, Jimena Andrea; Barrientos, Maria Jose; Sierpe, Victor; Huidobro, Consuelo; Christensen, Marianne; Araneda, Isidora; Cantarero, Catalina; Arecheta, Constanza; Morello Repetto, Flavia; San Roman Bontes, Manuel Julio (My University, 2025)
The results of a survey of the archaeological site of Tilly Este, located in the bay of the same name on Carlos III Island, Strait of Magellan, Chile, are presented. The site is a multicomponent maritime hunter-gatherer shell midden that includes pre-contact and post-contact historic occupations. The record indicates the presence of occupational events of different intensity including technology associated with a greater diversity of activities during historical times. The latter were associated with abundant green obsidian lithic materials and a bone industry that contrasts with pre-contact (sixteenth century) occupations. The zooarchaeological evidence (marine and terrestrial mammals, birds, fish and mollusks) shows the richness and biodiversity of the bay, and the area surrounding the island. The archaeological information, together with ethnohistorical observations and the presence of a fishing hedge in the area, indicate that this bay has played an important role in human activity for at least the last 1000 years.
Bahías protegidas y nodos de caza-pesca en las islas australes de Patagonia. El sitio canoero Tilly Este en isla Carlos III, estrecho de Magallanes (53ºS)
Keywords: marine hunter-gatherers; protected bay; biodiversity; patagonia; pre-contact and historical